Quantitating CD8+ T cell memory development - Nizharadze, Tamar; Becker, Nils B.; Höfer, Thomas (Trends in immunology, 2023)
In acute immune responses to infection, memory T cells develop that can spawn recall responses. This process has not been observable directly in vivo. Here we highlight the utility of mathematical inference to derive quantitatively testable models of mammalian CD8+ T cell memory development from complex experimental data. Previous inference studies suggested that precursors of memory T cells arise early during the immune response. Recent work has both validated a crucial prediction of this T cell diversification model and refined the model. While multiple developmental routes to distinct memory subsets might exist, a branch point occurs early in proliferating T cell blasts, from which separate differentiation pathways emerge for slowly dividing precursors of re-expandable memory cells and rapidly dividing effectors.
Online verfügbar: 4. Juni 2023, Artikelversion: 22. Juni 2023
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 25.08.2023